2017
DOI: 10.1016/j.physletb.2017.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing black holes in quantum gravity and the Fermi gamma-ray excess

Abstract: Non-perturbative quantum-gravity effects can change the fate of black holes and make them bounce in a time scale shorter than the Hawking evaporation time. In this article, we show that this hypothesis can account for the GeV excess observed from the galactic center by the Fermi satellite. By carefully taking into account the secondary component due to the decay of unstable hadrons, we show that the model is fully self-consistent. This phenomenon presents a specific redshift-dependance that could allow to dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 31 publications
1
32
0
1
Order By: Relevance
“…While what we said above holds in the case of shortlived bounces of typical timescale τ (1) , more complex is the case of long-lived bounces with τ = τ (2) , for which several phenomenological studies have been performed in the literature [52,53,164,165]. In this case no relevant signal is expected up to this timescale while two distinct components are predicted as being associated to the typical size of the exploding object (infrared component) and to the typical energy of the universe at the moment of its formation (ultraviolet component).…”
Section: Burstsmentioning
confidence: 91%
See 1 more Smart Citation
“…While what we said above holds in the case of shortlived bounces of typical timescale τ (1) , more complex is the case of long-lived bounces with τ = τ (2) , for which several phenomenological studies have been performed in the literature [52,53,164,165]. In this case no relevant signal is expected up to this timescale while two distinct components are predicted as being associated to the typical size of the exploding object (infrared component) and to the typical energy of the universe at the moment of its formation (ultraviolet component).…”
Section: Burstsmentioning
confidence: 91%
“…For primordial black holes whose lifetime is of the order of the Hubble time, it was shown that the infrared component of the signal could get up to the GeV scale and be peaked in the MeV, while the ultraviolet part of the burst is expected to be in the TeV range [164,165]. If confirmed by more accurate modelling, this would place the search for the bursts associated to bouncing geometries within the realm of current high energy astrophysics experiments (provided that a sufficient number of primordial black holes is created in the early universe).…”
Section: Burstsmentioning
confidence: 99%
“…Here we have assumed for simplicity that the internal volume v is conserved in this transition. A more precise account of this process will be studied elsewhere (for the tentative phenomenology derived from this process, see [33][34][35][36][37][38][39]).…”
Section: White To Black Instabilitymentioning
confidence: 99%
“…. Applying these field equations in the FRW metric (1), focusing on the flat case, and assuming the usual matter perfect fluid (12), one obtains the following modified Friedmann equations [51]:…”
Section: Finsler-like Gravity On a Tangent Bundlementioning
confidence: 99%
“…The violation of null energy condition needs to be handled with care, in order not to spoil the usual thermal history and the sequence of epochs after the bounce. Nevertheless, such violations can easily be acquired from modified [7] or quantum gravity [12]. In particular, they can be eas- * Electronic address: geminas@phys.uoa.gr † Electronic address: msaridak@phys.uoa.gr ‡ Electronic address: pstavrin@math.uoa.gr § Electronic address: alktrian@phys.uoa.gr ily acquired in the Pre-Big-Bang [13,14] and the Ekpyrotic [15,16] models, in gravity actions with higher order corrections [17,18], in f (R) gravity [19,20], in f (T) gravity [21], in braneworld scenarios [22,23], in non-relativistic gravity [24][25][26], in Galileon theory [27,28], in massive gravity [29], in Lagrange modified gravity [30], in loop quantum cosmology [31][32][33], etc.…”
Section: Introductionmentioning
confidence: 99%